1999
DOI: 10.1002/(sici)1098-2361(1999)18:6<551::aid-zoo9>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of lipids, vitamins A and E, vitamin D metabolites, and carotenoids in nine primate species at four zoos

Abstract: Data from population‐based case‐control studies of non‐Hodgkin's lymphoma among white men from Kansas, Nebraska, Iowa, and Minnesota were pooled to evaluate potential risks from environmental exposures in more detail, while controlling for potential confounding factors. These data provided the opportunity to evaluate the risk of non‐Hodgkin's lymphoma from potential exposures to lindane, a pesticide that causes cancer in laboratory animals and has been associated with human cancer in a few epidemiologic invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 18 publications
0
12
2
Order By: Relevance
“…As mentioned before, monkeys have significantly lower LDL cholesterol levels than Hominoids [22]. It is unknown whether the loss-of-function mutation in the C-terminal domain is a random phenomenon or a common feature that influences cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned before, monkeys have significantly lower LDL cholesterol levels than Hominoids [22]. It is unknown whether the loss-of-function mutation in the C-terminal domain is a random phenomenon or a common feature that influences cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…Significant differences in lipid profiles occur among primates; for example, New World and Old World monkeys have significantly lower serum total cholesterol, triglycerides, and LDL cholesterol levels than Hominoids [22]. Among Hominoids, gorillas have the highest circulating total cholesterol, triglycerides, and high-density lipoprotein (HDL) cholesterol levels [22]. Caceres et al [23] found that several genes related to lipid metabolism were differentially expressed in humans and non-human primates.…”
Section: Introductionmentioning
confidence: 99%
“…Triacylglycerides, total cholesterol and LDL‐Chol concentrations for the woolly monkeys were within the normal ranges for new and old world monkeys and for humans (Halperin et al., 1968; Cefalu et al., 1993; Crissey et al., 1999; Andrade et al., 2004; Kim et al., 2005; Medline Plus, 2006). However, the HDL‐Chol values appeared to be low (0.8 mmol/l) compared with the reference ranges for primates (Crissey et al., 1999; Medline Plus, 2006). Concentrations of HDL are inversely related to the incidence of cardiovascular disease (Lagua and Claudio, 2004).…”
Section: Discussionmentioning
confidence: 74%
“… *Numbers in superscript italics refer to the published references as follows: 1 = Brady, 2000; 2 = Simian, 2006; 3 = Ausman and Gallina, 1978; 4 = Lloyd et al., 1995; 5 = Crissey et al., 1999; 6 = Halperin et al., 1968; 7 = Cefalu et al., 1993; 8 = Kim et al., 2005; 9 = Mythili et al., 2005; 10 = Edwards et al., 2004; 11 = Kemnitz et al., 2002; 12 = Andrade et al., 2004; 13 = Guthrie and Guthrie, 2003; 14 = Merck, 1996; 15 = The Expert Committee on the Diagnosis of Diabetes Mellitus (ECDDM), 2003; 16 = Lagua and Claudio, 2004; 17 = Medline Plus, 2006. …”
Section: Resultsmentioning
confidence: 99%
“…The contents of a fecal sample, combined with observational data, help the nutritionist better understand what foods are being eaten, during which times of the year and in the captive diet, the effects of variation Deblauwe et al, 2003;Yamagiwa et al, , 2005Remis and Dierenfeld 2004). From a serum sample, the nutritionist measures circulating levels of vitamin metabolites, lipids, and carotenoids, which provide information on the animal's health, nutritional status, and the absorption levels of nutrients (Crissey et al, 1999).…”
Section: Health and Nutritionmentioning
confidence: 99%